Investigation of tool wear and chip formation on peck drilling of mild stell - Mohamad Khirul Azni Abu Bakar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
In drilling at the industry, the problem that always emerges is sever wear occurs at cutting tool and poor surface finish on part drilled. This is became of improper selection of cutting parameter that affects tothe cutting tool condition.